The interplay between hypoxia signalling and hepatitis B virus replication - Harris, JM (2021)
Viral replication is influenced by the host cell microenvironment, and local oxygen tension is a major factor that shapes the intracellular landscape. Hepatitis B virus (HBV) replicates in the liver which harbours a naturally low oxygen environment. However, in vitro culture systems apply atmospheric oxygen conditions, and so our understanding of the role of oxygen sensitive factors in the viral life cycle is limited.